A systematic review of the evidence for complementary and alternative medicine in infertility. Issue 3 (21st June 2013) - Clark, Natalie A.; Will, Matthew; Moravek, Molly B.; Fisseha, Senait
Abstract: Background: The use of complementary and alternative medicine (CAM) by patients and physicians has increased markedly in recent years. Many case reports, case series, and uncontrolled trials of varying quality have been completed; however, there is now a slowly increasing number of randomized controlled trials (RCTs) examining the use of CAM. Objectives: To identify, survey, and review RCTs investigating the use of CAM for infertility treatment. Search strategy: The MEDLINE and Cochrane databases were electronically searched. Selection criteria: RCTs examining modalities for treatment or improvement of health status were reviewed. Data collection and analysis: RCTs were included based on use of objective measures, articles written in English, availability through the University of Michigan database, and clear published clinical outcomes. Main results: Thirty‐seven articles assessing a variety of CAM modalities met inclusion criteria. Acupuncture, selenium supplementation, weight loss, and psychotherapeutic intervention had 3 or more studies demonstrating beneficial effect. Other interventions had been studied less and evidence for them was limited. Conclusions: Although there is preliminary evidence of the effectiveness of some CAM interventions among infertile patients, many of these interventions require further investigation before they can be considered for routine clinical use.